(untitled) (International Journal of Physiology, 2020)
Aim of Study: To evaluate the effects of Trataka yoga on neuropsychological functions in myopic subjects. Methodology: Out of 36 myopes recruited for the study, 25 subjects were considered for statistical analysis. Digit Span Test and Complex Figure test were measured before and after an intervention of Trataka yoga kriya for 3 weeks. Results: In the present study, post Trataka yoga kriya intervention, Complex figure test results showed an increase in mean scores from 31.32 to 34.20 and Digit span test results showed an increase in mean scores from 7.32 to 7.96, which was found to be statistically significant. Conclusion: Our study concluded that Trataka yoga has a significant effect on neuropsychological functions in myopes Further regular Trataka yoga kriya practice can be used as an inexpensive, simple and nonpharmacological means as a protective factor against cognitive deterioration.